Green-driven CaO catalyst for biodiesel production - Mahmood, Sarah S.; AL-Yaqoobi, Atheer M.; Rehman, Fahad (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
With increasing population and development, the resources of fossil fuels decreased, leading to the need to find alternative sources of energy. Furthermore, the use of fossil fuels is accompanied by several downsides including environmental fatality associated with toxic gas emissions from diesel engines and continuous increase of the price of diesel fuel. Biodiesel is one of the most important types of renewable energy that replaces the fossil fuel requirement (mineral diesel) and maintains eco-friendly sustainability. Calcium is an essential plant nutrient as it plays an important role in the formation of plant cell walls and membranes. Therefore, the fallen leaves of mango tree can be utilized to produce nano calcium oxide and serve as a highly effective catalyst in the transesterification process for biodiesel production. The green approach of mango leaves extract is more cost-effective, nontoxic, and environmentally friendly compared to other ways such as chemical and physical procedures. Transesterification reaction was conducted at fixed parameters of 65 ℃ reaction temperature, 3 wt.% catalyst concentration, 1.5 h reaction time, and 50% alcohol to oil weight ratio. The effects of several other parameters on the transesterification reaction were studied such as the volume of the reaction mixture, mixing speed, FFA% content, and methanol/ethanol weight ratio. The study found that methanol is more effective than ethanol as alcohol in transesterification reaction, and the FFA% has a slight effect on the catalyst to 1.8% FFA. The produced biodiesel was characterized by GC-MS and FT-IR analysis which indicate the presence of esters. The physical and fuel characteristics of the produced biodiesel were measured; it had a viscosity of 3.708 mm2/s, a density of 0.88869 g/cm3, and a flash point of 108 °C.